Doubled-up legume rotations improve soil fertility and maintain productivity under variable conditions in maize-based cropping systems in Malawi - Smith, A.; Snapp, Sieglinde S.; Dimes, John P.; Chikowo, Regis (Elsevier, 2016)
Smallholder farmers in Malawi must cope with small farm size, low soil fertility and production risks associated with rainfed agriculture. Integration of legumes into maize-based cropping systems is advocated as a means to increase production of diverse nutrient-dense grains and improve soil fertility. It is difficult to achieve both aims simultaneously, however. Short-duration grain legumes rarely produce enough biomass to appreciatively improve soils, and long duration pigeonpea, commonly grown in Malawi as a dual purpose crop, produces little or no edible grain as a consequence of grain-filling into the dry season. A novel technology is the doubled-up legume rotation (DLR) system in which two legumes with complementary phenology are intercropped and grown in rotation with maize. Initial performance from on-farm research is favorable; however, it is crucial to understand competition for resources in mixed cropping systems under variable soil and climate conditions. We used soil and crop yield data from farmer participatory trials to parameterize the Agricultural Production Systems Simulator (APSIM) and evaluate its performance in simulating observed treatments at three locations in central Malawi. We used the calibrated APSIM model to investigate the performance of DLR and other maize-based systems across 26 growing seasons (1979–2005) in the three agroecologies. We simulated two DLR systems (maize rotated with a groundnut/pigeonpea or soybean/pigeonpea intercrop), maize rotated with groundnut or soybean, maize intercropped with pigeonpea, and continuous maize under a range of N fertilizer inputs. We extended findings to the household level by determining calorie and protein yields of these systems, and calculating the chance that an average household could meet their food requirements by dedicating all available farmland to a given system. Simulated maize grain yields in DLR and maize-grain legume rotations were essentially equivalent, and exceeded yields in maize/pigeonpea intercrop and sole cropped maize receiving comparable fertility inputs. All rotation systems were more likely to meet household calorie and protein needs than other systems receiving equivalent inputs. DLR systems accumulated higher total soil C and N over time than traditional rotation systems in areas where pigeonpea performed well. However, the effects of improved soil fertility on maize yields were counterbalanced by factors including N immobilization and water availability. We conclude that where growing conditions allow, DLR can harness the complementary phenology of pigeonpea to build soil quality for the future without reducing maize yields or compromising household food production in the immediate term.